2022
DOI: 10.3390/ijms23179511
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Mycobacterium Infection: From the Immune System to Mitochondrial Haplogroups

Abstract: In humans, mitochondria play key roles in the regulation of cellular functions, such as the regulation of the innate immune response and are targets of several pathogenic viruses and bacteria. Mycobacteria are intracellular pathogens that infect cells important to the immune system of organisms and target mitochondria to meet their energy demands. In this review, we discuss the main mechanisms by which mitochondria regulate the innate immune response of humans to mycobacterial infection, especially those that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…Moreover, additional research will be conducted to comprehend the mechanism of infection-mediated neuroinflammation, with a specific focus on the role of mitochondria dysfunction. Mitochondria dysfunction has been associated with the development of both MS and EAE [39,40], as well as mycobacterial infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional research will be conducted to comprehend the mechanism of infection-mediated neuroinflammation, with a specific focus on the role of mitochondria dysfunction. Mitochondria dysfunction has been associated with the development of both MS and EAE [39,40], as well as mycobacterial infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…Neben der Energieproduktion sind Mitochondrien an der Regulation der Apoptose (Zelltod) und der Produktion reaktiver Sauerstoffspezies (ROS) beteiligt. Dadurch sind Mitochondrien Teil von komplexen Zellkommunikationspro-zessen, die zur Homöostase des menschlichen Organismus beitragen können [8].…”
Section: Mitochondriale Dysfunktionunclassified
“…Notably, M. leprae is dependent on the production of energy and nutritional products by the host, resulting from the host–pathogen interaction, undoubtedly involving the main function of mitochondria of energy generation, due to the cellular signaling pathways in which these organelles participate and connect their metabolism to meet their nutrient demands 6 , 7 . Furthermore, due to the decay of the M. leprae genome, which leads to strain uniformity, it is suggested that the genetic background of the host, and not bacterial variability, is a central aspect of susceptibility to leprosy 1 .…”
Section: Introductionmentioning
confidence: 99%